2019
DOI: 10.1007/s00383-019-04610-1
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative treatment for nonperforated appendicitis in children: a systematic review and meta-analysis

Abstract: Acute appendicitis is the most common surgical emergency in children. Nonoperative treatment of nonperforated acute appendicitis in children is an alternative to appendectomy. The purpose of this systematic review and meta-analysis was to determine the outcomes of nonoperative treatment of nonperforated acute appendicitis in children in the literature. Databases were searched to identify abstracts, using predefined search terms. The abstracts were reviewed by two independent reviewers and articles were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
53
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 38 publications
4
53
1
5
Order By: Relevance
“…Kessler et al[15] determined that the operative treatment group yielded a 98% effectiveness, while the non-operative treatment (NOT) group resulted in a significantly lower 74% effectiveness rate. This contrasts the rather positive findings of Georgios et al[14] who found a 97% success rate with NOT, and Maita et al[16], who found a 92% effectiveness with NOT in their meta-analyses.Not surprisingly, results of individual control trials and studies are similar in their disagreement. Knappen et al[5] used a prospective cohort study of 45 children aged 7-17 years from multiple institutions to study the success rate of NOT of acute uncomplicated appendicitis (AUA).…”
Section: Introductioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Kessler et al[15] determined that the operative treatment group yielded a 98% effectiveness, while the non-operative treatment (NOT) group resulted in a significantly lower 74% effectiveness rate. This contrasts the rather positive findings of Georgios et al[14] who found a 97% success rate with NOT, and Maita et al[16], who found a 92% effectiveness with NOT in their meta-analyses.Not surprisingly, results of individual control trials and studies are similar in their disagreement. Knappen et al[5] used a prospective cohort study of 45 children aged 7-17 years from multiple institutions to study the success rate of NOT of acute uncomplicated appendicitis (AUA).…”
Section: Introductioncontrasting
confidence: 85%
“…[1]Yet treating pediatric acute appendicitis non-operatively rather than by open or laparoscopic appendectomy still elicits great debate,[24]spawned by the results of control trials and observational studies[59], reviews[1013] and meta-analyses. [1416]The meta-analyses are not in agreement. Kessler et al[15] determined that the operative treatment group yielded a 98% effectiveness, while the non-operative treatment (NOT) group resulted in a significantly lower 74% effectiveness rate.…”
Section: Introductionmentioning
confidence: 97%
“…They also reported that 16% later on needed appendectomy due to recurrent appendicitis. 9 Huang L et al reported 90.5% success rate of NOT for acute uncomplicated appendicitis in a previous metaanalysis. 10 Bachur and co-authors analyzed data of various United States' hospitals retrospectively and revealed that NOT was associated with more emergency visits and hospitalization, and ultimately 46% had appendectomy in one year follow up, thus necessitating the need for further multi-centric RCT.…”
Section: Introductionmentioning
confidence: 97%
“…Still to establish efficacy of NOT in children further randomized controlled trials (RCT) are needed. 8,9 Sonia Maita and co-authors in a recent metaanalysis reported success rate of NOT as 92% after analyzing the published literature. They also reported that 16% later on needed appendectomy due to recurrent appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to new conservative modalities for the treatment of uncomplicated acute appendicitis, current strategies for the distinguishment of high risk and low risk acute appendicitis are under pressure. Successful and safe application of conservative antibiotic treatment for clinically uncomplicated appendicitis has been demonstrated [ 1 ]. Even frequent spontaneous resolution of histologically phlegmonous appendicitis has been claimed [ 2 ].…”
Section: Introductionmentioning
confidence: 99%